Role of Energy Security Tradeoffs and Cooperation for Wireless Ad-Hoc Networks: Exploring Energy Security Tradeoffs and Cooperative Behavior in Wireless Ad-Hoc Networks (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In this paper we discuss the security energy tradeoffs that exist in wireless ad hoc networks. Based on energy and security costs, we formulate a game theoretic distributed monitoring algorithm that enforces cooperative behavior for individual nodes by reward functions. Various energy security tradeoffs operating points for the networks intrusion detection can be achieved by tuning the rewards parameter.